2019
DOI: 10.1016/j.matbio.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium activated nucleotidase 1 (CANT1) is critical for glycosaminoglycan biosynthesis in cartilage and endochondral ossification

Abstract: Desbuquois dysplasia type 1 (DBQD1) is a chondrodysplasia caused by mutations in CANT1 gene encoding an ER/Golgi calcium activated nucleotidase 1 that hydrolyses UDP. Here, using Cant1 knock-in and knock-out mice recapitulating DBQD1 phenotype, we report that CANT1 plays a crucial role in cartilage proteoglycan synthesis and in endochondral ossification. Specifically, the glycosaminoglycan synthesis was decreased in chondrocytes from Cant1 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 45 publications
(64 reference statements)
8
37
0
2
Order By: Relevance
“…In skin fibroblasts from patients with DBQD1, ER enlargement with retention of proteinaceous material has been observed . The same findings have been reported in cartilage from a Cant1 knock‐out mouse; however, ER enlargement does not trigger ER stress and conventional unfolded protein response (UPR) despite reduced PG secretion . Lastly, confocal microscopy in skin fibroblasts from patients with mutations in SLC10A7 has demonstrated enlargement of the Golgi due to post‐Golgi transport defects through the secretory pathway .…”
Section: Intracellular and Extracellular Consequences Of The Defects mentioning
confidence: 99%
See 2 more Smart Citations
“…In skin fibroblasts from patients with DBQD1, ER enlargement with retention of proteinaceous material has been observed . The same findings have been reported in cartilage from a Cant1 knock‐out mouse; however, ER enlargement does not trigger ER stress and conventional unfolded protein response (UPR) despite reduced PG secretion . Lastly, confocal microscopy in skin fibroblasts from patients with mutations in SLC10A7 has demonstrated enlargement of the Golgi due to post‐Golgi transport defects through the secretory pathway .…”
Section: Intracellular and Extracellular Consequences Of The Defects mentioning
confidence: 99%
“…Besides altered sulfation in disorders linked to proteins and enzymes involved in the sulfate activation pathway, CS sulfation imbalance with an increased percentage of nonsulfated disaccharide has been reported in the limb of the Chsy1 knock‐out mouse . Altered CS sulfation has also been detected in chondrocyte cultures and in cartilage of the Cant1 knock‐out mouse . Moreover, in cartilage explants from mouse models of DBQD1 and Schneckenbecken dysplasia CS chains with reduced length have been detected .…”
Section: Intracellular and Extracellular Consequences Of The Defects mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, CANT1 is a nucleotidase that preferentially hydrolyzes UDP to UMP and phosphate [16–18]. CANT1 has also been predicted to be involved in GAG synthesis, and the recent study using genetically modified mice has confirmed the prediction [6–8,19].…”
Section: Introductionmentioning
confidence: 99%
“…Paganini and colleagues generated two mouse strains by an ES cell‐based method: a Cant1 knockout (KO) and a Cant1 knock‐in harboring DD type 1 causative p.R302H missense mutation [19]. Both strains present skeletal dysplasia phenotypes similar to DD type 1.…”
Section: Introductionmentioning
confidence: 99%